Silage Fermentation Quality, Anthocyanin Stability, and in vitro Rumen Fermentation Characteristic of Ferrous Sulfate Heptahydrate-Treated Black Cane (Saccharum sinensis R.) - Suong, Ngo Thi Minh; Paengkoum, Siwaporn; Salem, Abdelfattah Zeidan Mohamed; Paengkoum, Pramote; Purba, Rayudika Aprilia Patindra (Frontiers in Veterinary Science, 2022)
Pretreatment of lignocellulose agricultural biomass with iron prior to ensiling is required to accelerate biomass breakdown during fermentation, which could result in functional microorganisms and chemicals that reduce nutrition loss, harmful substances, and improve animal performance. The objective of this study was to investigate the effects of increasing dilutions of ferrous sulfate heptahydrate (FS) pretreatment at fresh matter concentrations of 0, 0.015, and 0.030% on the fermentation quality of black cane (BC) silage, anthocyanin stability, ruminal biogas, rumen fermentation profile, and microbial community. Pre-ensiled and silage materials were evaluated. High moisture, fiber, anthocyanin, and lignification of biomass, as well as undesirable ensiling microorganisms, were found in BC' pre-ensiled form. Increasing dilutions of FS incorporated into silages were observed to linearly decrease dry matter, anthocyanin, and nutritive value losses. The lignin values decreased linearly as the percentage of FS increased up to 0.030%. Given that the ruminants were fed pre-ensiled materials, BC silage treated with 0.030% FS dilution had comparable results to pre-ensiled BC in terms of increasing in vitro volatile fatty acid concentrations, maintaining total gas production, and reducing methane production, when compared to other FS-treated silages. In addition, BC silage treated with a 0.030% FS dilution inhibited methanogenic bacteria and regulated cellulolytic bacteria in rumen fluid. Overall, the anthocyanin content of BC remained constant throughout the rumen fermentation process after increasing dilutions of FS, indicating that BC is a viable ruminant feedstock and that pretreatment of BC with dilute FS-assisted ensiling at 0.030% could be used to generate ruminant diets.